The Attributable Proportion of Specific Leisure-Time Physical Activities to Total Activity Volume Among US Adults, National Health and Nutrition Examination Survey 1999–2006 - Watson, Kathleen B. (J Phys Act Health, 2016)
BACKGROUND: Previous studies have examined participation in specific leisure-time physical activities (PA) among US adults. The purpose of this study was to identify specific activities that contribute substantially to total volume of leisure-time PA in US adults. METHODS: Proportion of total volume of leisure-time PA moderate-equivalent minutes attributable to 9 specific types of activities was estimated using self-reported data from 21,685 adult participants (≥ 18 years) in the National Health and Nutrition Examination Survey 1999–2006. RESULTS: Overall, walking (28%), sports (22%), and dancing (9%) contributed most to PA volume. Attributable proportion was higher among men than women for sports (30% vs. 11%) and higher among women than men for walking (36% vs. 23%), dancing (16% vs. 4%), and conditioning exercises (10% vs. 5%). The proportion was lower for walking, but higher for sports, among active adults than those insufficiently active and increased with age for walking. Compared with other racial/ethnic groups, the proportion was lower for sports among non-Hispanic white men and for dancing among non-Hispanic white women. CONCLUSIONS: Walking, sports, and dance account for the most activity time among US adults overall, yet some demographic variations exist. Strategies for PA promotion should be tailored to differences across population subgroups.